Pressure Prediction by Programme Logic Control Approach on Superplastic Forming in 7075 Al Alloy - M. Balasubramanian (Journal of Basic & Applied Sciences, 2021)
A widespread problem in a superplastic forming process is to obtain a uniform thickness distribution in multiple geometry components. Hence, nowadays, the variable pressure control approach has been implementing in order to obtain uniform thickness variation in complex profiles. This paper observed the outcome of various stages in the superplastic forming process for multistage hemispherical die cavity in a newly developed pressure prediction method. Superplastic behaviour such as forming pressure, forming temperature, forming time and thickness distribution are analysed and optimised all parameters in multi-stage profile by using a new pressure prediction approach. Experimentally and numerically evaluated the superplastic parameters and the values are obtained from finite element methods agrees well with the experimental results.